Erosion of organic carbon from the Andes and its effects on ecosystem carbon dioxide balance. Issue 3 (6th March 2017) - Clark, K. E.; Hilton, R. G.; West, A. J.; Robles Caceres, A.; Gröcke, D. R.; Marthews, T. R.; Ferguson, R. I.; Asner, G. P.; New, M.; Malhi, Y.
Abstract: Productive forests of the Andes are subject to high erosion rates that supply to the Amazon River sediment and carbon from both recently photosynthesized biomass and geological sources. Despite this recognition, the source and discharge of particulate organic carbon (POC) in Andean Rivers remain poorly constrained. We collected suspended sediments from the Kosñipata River, Peru, over 1 year at two river gauging stations. Carbon isotopes ( 14 C, 13 C, and 12 C) and nitrogen to organic carbon ratios of the suspended sediments suggest a mixture of POC from sedimentary rocks (POCpetro ) and from the terrestrial biosphere (POCbiosphere ). The majority of the POCbiosphere has a composition similar to surface soil horizons, and we estimate that it is mostly younger than 850 14 C years. The suspended sediment yield in 2010 was 3500 ± 210 t km −2 yr −1, >10 times the yield from the Amazon Basin. The POCbiosphere yield was 12.6 ± 0.4 t C km −2 yr −1 and the POCpetro yield was 16.1 ± 1.4 t C km −2 yr −1, mostly discharged in the wet season (December to March) during flood events. The river POCbiosphere discharge is large enough to play a role in determining whether Andean forests are a source or sink of carbon dioxide. The estimated erosional discharge of POCpetro from the Andes is much larger ( 1 Mt C yr −1 ) than the POCpetro discharge by the Madeira River downstream in the Amazon Basin, suggesting that oxidation of POCpetro counters CO2 drawdown by silicate weathering. The flux and fate of Andean POCbiosphere and POCpetro need to be better constrained to fully understand the carbon budget of the Amazon River basin. Key Points: Quantify discharge of suspended sediment and particulate organic carbon (biospheric and petrogenic) by an Andean River The fate of river biospheric particulate organic carbon determines whether Andean forest is a carbon dioxide source or sink Oxidation of petrogenic particulate organic carbon eroded from the Andes counters CO2 drawdown by silicate weathering in the lowlands